2010
DOI: 10.1002/hlca.201000102
|View full text |Cite
|
Sign up to set email alerts
|

Artabotryols A – E, New Lanostane Triterpenes from the Seeds of Artabotrys odoratissimus

Abstract: Six new lanostane triterpenes, artabotryols A, B, C1, C2, D, and E (1, 2, 3a, 3b, 4, and 5, resp.) have been isolated from the seeds of Artabotrys odoratissimus (Annonaceae). Their structures have been established as (3a,22S,25R)-3-hydroxy-22,26-epoxylanost-8-en-26-one (1), (3a,22S,25R)-22,26-epoxylanost-8-ene-3,26-diol (2), (3a,22S,25R,26R)-26-methoxy-22,26-epoxylanost-8-en-3-ol (3a), (3a,22S,25R, 26S)-26-methoxy-22,26-epoxylanost-8-en-3-ol (3b), (3a,22S,25R)-3,22-dihydroxylanost-8-en-26-oic acid (4) and (3a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The result showed that the 1 H NMR of compound 2 agreed 21 As a result, compound 2 was identified to be a C-25 epimer of 3-epi-astrahygrol named astraodorol, found for the first time in Astraeus spp. However, a similar structure had been reported as an Artabotryols A, 17 isolated from the seeds of Artabotrys odoratissimus. Therefore, compound 2 is a known compound.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…The result showed that the 1 H NMR of compound 2 agreed 21 As a result, compound 2 was identified to be a C-25 epimer of 3-epi-astrahygrol named astraodorol, found for the first time in Astraeus spp. However, a similar structure had been reported as an Artabotryols A, 17 isolated from the seeds of Artabotrys odoratissimus. Therefore, compound 2 is a known compound.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…1). The analysis of the above data and a comparison of the 1 H and 13 C NMR spectral data with literature, showed that compound 2 was a C-3 oxidative of the known artabotryol C1, isolated from the seeds of Artabotrys odoratissimus (Gupta et al, 2010). The correlation between HC-OMe and H-20 in NOESY suggested an R configuration at C-26.…”
Section: Resultsmentioning
confidence: 89%
“…1). Spectroscopic data suggested that 3 was a new methylation form of artabotryol D (Gupta et al, 2010). The stereochemistry at C-3, C-20, C-22 and C-25 were assigned as 3a, 22S, 25R, according to its identical 1 H and 13 C NMR data to that of artabotryol D.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations